2016
DOI: 10.1177/0897190016645023
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Point-of-Care Testing for Community Pharmacies: A Review of the Current Literature

Abstract: The current literature suggests that POCTs in community pharmacies assist with patient outcomes by providing screenings and referring patients with dyslipidemia for further evaluation. The majority of studies on cholesterol POC devices focused on accuracy, revealing the need for further studies to develop best practices and practice models with successful reimbursement. Accuracy, device specifications, required supplies, and patient preference should be considered when selecting a POC device for purchase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The device used in the present study for the analysis of cholesterol levels has shown good accuracy compared to other brands and models. Since dyslipidemia is a risk factor for cardiovascular disease, it is recommended to screen populations; thus, the use of fingertip devices appears to be an appropriate alternative 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The device used in the present study for the analysis of cholesterol levels has shown good accuracy compared to other brands and models. Since dyslipidemia is a risk factor for cardiovascular disease, it is recommended to screen populations; thus, the use of fingertip devices appears to be an appropriate alternative 15 .…”
Section: Discussionmentioning
confidence: 99%
“…We used a smartphone-based, easy-to-use, intuitive user interface ( Figure 2) [12,13]. Smartphone-based point-of-care blood tests have several advantages in terms of computation, communication, usability, and cost-effectiveness [14,15]. In addition, data generated from point-of-care devices can be easily shared with caregivers and healthcare professionals, helping to manage chronic disease in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists’ experience with other POC tests may inform their use of POC PGx testing and anticipated problems. A recent review of pharmacists’ use of POC testing for cholesterol found a positive impact on screening and identifying patients for referral for dyslipidemia [125]. In a health system, a pharmacist-operated anticoagulation clinic demonstrated reduced hospitalizations and increased time within the therapeutic range with a POC intervention [126].…”
Section: Challenges In Implementing Poc Pgx Testingmentioning
confidence: 99%
“…For example, POC creatinine testing can be administered by the pharmacist to patients with unknown renal status impairment; consultation with the physician can lead to changes in medication dosing and improved outcomes [127]. Reimbursement for POC testing will likely remain a major issue for pharmacists, regardless of test type [125,128]. Since state pharmacy boards define the scope of practice for pharmacists, a published review of pharmacy regulations reported that fewer than 20 percent of states addressed POC [129].…”
Section: Challenges In Implementing Poc Pgx Testingmentioning
confidence: 99%